2015
DOI: 10.3920/bm2014.0031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacillus subtilis R0179 on gastrointestinal viability and general wellness: a randomised, double-blind, placebo-controlled trial in healthy adults

Abstract: A probiotic formulation of Enterococcus faecium R0026 and Bacillus subtilis R0179 has been evaluated in previous clinical trials. However, B. subtilis R0179 has not been evaluated as a single probiotic strain or in combination with other strains at doses higher than 0.1×109 cfu. To establish oral dose-response tolerance and gastrointestinal (GI) viability of B. subtilis R0179, a randomised, double-blind, placebo-controlled trial in healthy adults (n=81; 18-50 years old) was conducted. Participants received B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 13 publications
0
50
1
1
Order By: Relevance
“…Although developed for patient populations, the GSRS has been used to evaluate gastrointestinal symptoms in healthy adults (5153). This study provides supporting data that the tool is sufficiently sensitive to detect differences in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although developed for patient populations, the GSRS has been used to evaluate gastrointestinal symptoms in healthy adults (5153). This study provides supporting data that the tool is sufficiently sensitive to detect differences in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There are risks associated with any treatment intervention; however, with regard to probiotics, this risk is low. Randomised clinical trials have examined the safety of probiotics, and shown them to be well-tolerated and associated with few adverse events in healthy individuals in dosages exceeding those used in the current study (32)(33)(34) . Given the significant clinical relevance of reducing the length of DLD events arising from AAD, one could affirm that the benefits of probiotic supplementation greatly outweigh the risks.…”
Section: Risk/benefitmentioning
confidence: 97%
“…Most evidence supporting beneficial effects of probiotic microorganisms stems from animal and human studies extrapolating from stool microbiome analysis or probiotics quantification to potential impacts of probiotics on host physiology (McNulty et al, 2011, Maldonado-Gó mez et al, 2016, Lahti et al, 2013, Hanifi et al, 2015, Wang et al, 2015, Eloe-Fadrosh et al, 2015, Charbonneau et al, 2013, Ferrario et al, 2014. To assess whether stool microbiome represents an accurate marker of upper and lower GI mucosal and luminal microbiome configuration, we performed the MUSPIC1 (MUcosal Search for Probiotic Impact and Colonization 1) study in mice and in humans.…”
Section: Murine Stool Microbiome Partially Correlates With the Gut Mumentioning
confidence: 99%